PRONUNCIATION COMPLICATIONS OF EFL LEARNERS. LITERATURE REVIEW - Aliyeva Nargiza Ravshanjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
English pronunciation is complex thing to learn and teach without proper instructions and training with natives, although in many countries English taught and second or foreign language and causes many troubles in pronouncing the words of this language. There are a great deal of problems in pronouncing the souns and reading, such as substitution of consonant sounds, vowel and diphtong sounds in pronouncing, in many different country students such as, chinese, arabic, thai and other students. In this article we endeavour to review all the problems of pronouncing foreign sounds of words by reviewing the researches conducted in this relevant theme by language scientists.